Prognostic Relevance of Significantly Raised CA 19-9 with Choledocholithiasis to Malignant Pathologies of HBS: An Early Experience in Dept. of Hepatobiliary Surgery at ShSMCH, Dhaka - Ahmed, Akhter; Shahriar, Shaon; Shimu, Farhana; Alam, SM Syeed Ul; Sarker, Rajib Dey (Journal of Shaheed Suhrawardy Medical College, 2020)
Background: Conventionally it is assumed that raised level of CA 19-9 (Carbohydrate antigen 19-9) is related to malignancies of liver, pancreas and biliary tract. Through our early experience in Shaheed Suhrawardy Medical College Hospital we found that raised level of CA 19-9 is not associated only with malignancies but also with other benign disorders of HBS. The aim of this study was to explore the relationship of raised CA 19-9 with hepatobiliary disorders other than malignancies. Result: We encountered a total of 57 cases at our department of Hepatobiliary Surgery where patients presented with classical features of obstructive jaundice with pain, anorexia and vomiting. Routine investigations of USG and MRCP revealed stone disease in the CBD. Fiftyseven patients with obstructive jaundice were studied retrospectively. Serum CA19-9 levels and some additional biochemical parameters were evaluated before and after treatment. CA 19-9 levels were significantly elevated in most patients, along with levels of total bilirubin, alkaline phosphatase (ALP), and gamma glutamyl transpeptidase (GGT), and 10 patients with benign disorders had extraordinarily high levels of these markers (> 1000 U/mL). The mean CA 19-9 level in the malignant group was greater than that in the benign group (826.83 ± 557.34 vs. 401.92 ± 483.92 U/mL, P = 0.005), and the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for CA19-9 were 100%, 7.69%, 33.33% and 47.47%, respectively. CA19-9 levels in the whole cohort were correlated with ALP (r = 0.77, P < 0.001), GGT (r = 0.83, P < 0.001), bilirubin (r = 0.69, P < 0.001), and CRP (r = 0.37, P = 0.004). The reduction in serum level of CA19-9 after treatment in the malignant group was remarkably less than that observed in the benign group (97.26 ± 123.24 U/mL vs. 352.71 ± 397.29 U/mL, P < 0.001). CA 19-9 levels may not be sufficient to distinguish between malignant and benign obstructive jaundice diseases. So raised CA 19-9 can obviously denote any hepatobiliary disease other than malignancy that will start to decline 1 to 28 days later after extraction of stone. Conclusion: In conclusion, it is obvious that raised level of CA 19-9 is associated not only with malignancies but also with other benign disorders of HBS to a larger scale. J Shaheed Suhrawardy Med Coll, December 2019, Vol.11(2); 119-123